Evaluation Of Diuretic Effect Of Ethanolic Seed Extracts Of Macrotyloma Uniflorum And Cucumis Melo In Rats - K.RAVISHANKAR,; P.S.V.VISHNU PRIYA, (International Journal of Pharma and Bio Sciences, 2012)
The present study was undertaken to investigate the diuretic effect of ethanolic seed extracts of Macrotyloma uniflorum and Cucumis melo in Albino rats. Ethanolic extracts of the seeds were administered to experimental rats orally at doses of 200mg/kg and 400mg/kg each p.o. Furosemide (5mg/kg) was used as a standard. The diuretic effects of the extracts were evaluated by measuring the Urine volume, Sodium, Potassium, Chloride and Bicarbonate contents. A significant Diuretic effect was observed from the experimental animals treated with extracts of Macrotyloma uniflorum and Cucumis melo individually compared to the control. Further, extract of Cucumis melo (400mg/kg) showed more diuretic effect than standard. This might be the first formal report on diuretic effects of both extracts individually. The results, to some extent explains the use of Macrotyloma uniflorum and Cucumis melo as a cure for renal diseases in Indian traditional medical practice.1